Antibiotic Sensitivity and Resistance Patterns in Complicated Urinary Tract Infections - Ghazala Shaheen, Sami ur Rahman, Sajid Malik, Muhammad Akhtar, Hassan ur Rahman Khan, Aftab Hussain Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: It is important to diagnose UTIs and identify the bacteria causing them in order to choose the best antibiotic treatment and prevent the emergence of antibiotic resistance. Objective: The aim of this study was to determine the antibiogram in Complicated Urinary Tract Infections at tertiary care hospital. Material and Methods: The current cross-sectional multicentre study was carried out at MMC, DHQ hospital Kohat, AWKUM, KUST from February 2023 to August 2023 after taking permission from the ethical committee of the institute. A total of 127 individual with complex urinary tract infections of both genders and different age group (16 to 80) years were included. Midstream urine samples were taken in sterile containers from each individual and were sent immediately to the microbiology lab for culturing. Samples were stored at 4°C if they were delayed. These samples were inoculated on blood agar and MacConkey and incubated for 24-48 hours and colonies were counted according to the lab protocols. Severe bacteriuria was defined as growth of greater than 105 CFU/mL. Antibiotic susceptibility profile was done using both disc diffusion and the VITEK-2 compact system direct Antimicrobial Susceptibility Testing (AST). The isolated bacteria were tested for sensitivity to commonly prescribed drugs. All the data was analyzed using SPSS version 26. Results: A total of 127 individuals were examined in this study out of which 43.3% were male and 56.65% were female. The most prevalent uropathogen in our study was E. Coli which was followed by Staphlococcus aureus and Klebsiella pneumoniae . E.coli was highly sensitive to colistin followed by fosfomycin, imipenem, meropenem, Amikacin, Nitrofurantoin ,Piperacillin / Tazobactum and ciprofloxacin while it was highly resistant to Cefixime followed by Co amoxiclave and Co-trimoxizole respectively. Similarly K Pneumoniae was 100% resistant to ciprofloxacin, levofloxacin and moxifloxacin while sensitive to imipenem and meropenem. P.uroginosa was 100% resistant to trimoxizole, ciprofloxacin levofloxacin and colisten. S.aureus was (100%) sensitive to Piperacillin/Tazobactum followed by imipenem and leofloxacin respectively while 100% resistant to moxifloxacin, nitrofurantoin and cefixime. Conclusion: The present study concluded that the most prevalent bacteria causing urinary tract infections are E. coli followed by S. aureus and K. pneumonia. Most of these bacteria were sensitive to imipenem and meropenem and resistant to commonly prescribed antibiotics. Keywords: Antibiotic Sensitivity; Resistance; Urinary Tract Infections.